2007
DOI: 10.2174/157339607780599047
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Viruses, Eosinophil Activation, and Early Allergen Sensitization - Early Life Predictors of Persistent Wheezing and Asthma

Abstract: Approximately 20% of all children will suffer from wheezing illnesses, and in 1-3% of all infants, respiratory distress is severe enough to require hospitalization. As wheezing infants form a heterogeneous group with different phenotypes and outcomes, it is still a challenge to identify those who will go on wheezing to develop asthma. In order to facilitate the prediction of later asthma, algorithms have been developed for clinical use. The algorithms validated this far are based on personal atopic findings an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2008
2008
2008
2008

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 149 publications
1
1
0
Order By: Relevance
“…Early exposure to furry animals leading to sensitization was found to be associated with increased bronchial responsiveness at school age. That is consistent with current literature stressing the role of sensitization to inhalant allergens as a predictor of persistent wheezing 27,28 . In addition, rhinovirus infection‐induced wheezing in infancy was associated with increased bronchial responsiveness at school age.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Early exposure to furry animals leading to sensitization was found to be associated with increased bronchial responsiveness at school age. That is consistent with current literature stressing the role of sensitization to inhalant allergens as a predictor of persistent wheezing 27,28 . In addition, rhinovirus infection‐induced wheezing in infancy was associated with increased bronchial responsiveness at school age.…”
Section: Discussionsupporting
confidence: 92%
“…The authors did not specify the viral etiology of wheeze in RSV‐negative children, and the role of rhinoviruses, for instance, remained open. Rhinoviruses, however, are commonly encountered in wheezing children in early childhood, 28 and often precipitate asthma symptoms in school children 30 . In addition, studies on experimental rhinovirus infections in adults have reported increased airway responsiveness in allergic subjects compared with non‐allergic ones, 31 and significantly reduced FEV 1 in home recordings by patients with mild atopic asthma 32 .…”
Section: Discussionmentioning
confidence: 99%